Possible involvement of IL‐6‐producing tissue‐resident macrophages in early‐onset pericardial effusion pathogenesis after hematopoietic stem cell transplantation. Issue 6 (31st January 2018) - Hamada, Satoru; Miyamoto, Jiro; Oshiro, Tokiko; Yagi, Takeshi; Kiyuna, Shinobu; Uehara, Taichi; Matsuda, Takehiro; Higa, Takeshi; Hyakuna, Nobuyuki; Nakanishi, Koichi
Abstract: Purpose: Pericardial effusion (PE) is a potentially life‐threatening complication following hematopoietic stem cell transplantation (HCT). A higher incidence of early‐onset PE, unrelated to graft‐versus‐host disease, before day 100 after HCT has been reported in pediatric patients, but the pathogenic mechanism is poorly understood. Aiming to determine the pathogenesis of early‐onset PE in pediatric patients, we analyzed the cytokine concentration and cell population in the pericardial fluid of four pediatric patients with PE. Methods: Between January 2009 and December 2015, four patients requiring pericardiocentesis for clinically significant PE were identified in 60 patients. We evaluated the interleukin‐6 (IL‐6), interferon‐γ, IL‐1β, and tumor necrosis factor‐α levels in PE. Two patients were available for analysis with intracellular cytokine flow cytometry and a chimerism assay. Results: All patients showed the accumulation of pericardial macrophages and high concentrations of IL‐6 in PE. Notably, the accumulated pericardial macrophages were CD163 + CD15 + CD14 + cells of host origin that produced IL‐6. Conclusion: These IL‐6‐producing tissue‐resident macrophages may be key players in the pathogenesis of early‐onset PE.